A Sufficient Condition for Rigidity in Extremality of Teichmüller Equivalence Classes by Schwarzian Derivative (Analysis in Theory and Applications, 2014)
The Strebel point is a Teichmüller equivalence class in the Teichmüller spacethat has a certain rigidity in the extremality of the maximal dilatation. In this paper,we give a sufficient condition in terms of the Schwarzian derivative for a Teichmüllerequivalence class of the universal Teichmüller space under which the class is a Strebelpoint. As an application, we construct a Teichmüller equivalence class that is a Strebelpoint and that is not an asymptotically conformal class.
Keywords: Strebel points; the Schwarzian derivative; asymptotically conformal maps.